Technological resources for English language teaching in middle school in a public school in Capitán Miranda, Itapúa (UNIHumanitas, 2024)
The context of the cessation of face-to-face classes due to the Covid 19 Pandemic led educational institutions to develop classes virtually at all levels. This work describes the technological resources used for teaching English as a foreign language in a school in the district of Capitán Miranda in 2021. It is framed in the line of educational technologies used for teaching the English language considering the points of view of the students and the teacher, based on what is indicated by the Ministry of Education and Sciences. The methodology was based on techniques that led to student surveys and interviews with the English language teacher to recollect information; It also relied on the analysis of the documentation available from the MEC for the implementation of virtual education in the context of the Covid 19 Pandemic. The MEC offered the platform "Tu escuela en casa" and Microsoft Teams for interaction between students and teachers, as well as monitoring. During the teaching-learning process of English as a foreign language, only WhatsApp, an instant messaging social network, was used as an intangible resource, and the most used tangible resource was the smartphone. Finally, a significant experience for students and teachers was the exchange of audio messages in English to practice pronunciation, which motivated and supported the development of the class guides received from the MEC. The effectiveness of technological resources for teaching the English language in this institution depends on tangible resources and the connectivity to access intangible resources.
Keywords: Virtual education; English language teaching; foreign language; technological resources